Effect of season on some fertility parameters of dairy and beef cows in Elazi? province - Sönmez, Mustafa; Demirci, Eşref; Türk, Gaffari; Gür, Seyfettin (My University, 2005)
This study was conducted to investigate the effects of seasons on some fertility parameters of dairy and beef cows in Elazi? province. A total of 511 multiparous dairy and beef cows in four commercial herds were used as material in the study. Climatic data were obtained from reports prepared at the Department of Meteorology in Elazi?. Daily maximum, minimum and average ambient temperatures and relative humidity were recorded throughout the year. Estruses were detected by observation twice a day. The expression of overt estrus was evaluated observing the degrees of signs of estrus. Cows were inseminated artificially after about 12 h from beginning estrus. First-service conception rates were determined by rectal palpation on the 75th day after insemination. Intensity of estrus signs were significantly affected by the seasons, especially in dairy cows. While the expression of overt estrus decreased in the cows inseminated during the hot months of the year, it increased in spring compared to the other seasons. The cows inseminated in summer had significantly lower conception rates than cows inseminated in other seasons. Moreover, this decrease in conception rate in dairy cows appeared to be carried into autumn. In conclusion, heat stress during summer resulted in a decrease in the exhibition of estrus behavior and conception rates of dairy and beef cows. Therefore, additional reproductive strategies are needed to counteract the adverse effect of heat stress on fertility during summer. © TÜBİTAK.
Keywords: Conception rate; Cow; Fertility; Heat stress; Season